2023
DOI: 10.7717/peerj.15800
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Grinnellian niche space of the cryptic species complex Gammarus roeselii

Abstract: Background The discovery of cryptic species complexes within morphologically established species comes with challenges in the classification and handling of these species. We hardly know to what extent species within a species complex differ ecologically. Such knowledge is essential to assess the vulnerability of individual genetic lineages in the face of global change. The abiotic conditions, i.e., the Grinnellian niche that a genetic lineage colonizes, provides insights into how diverse the ecological requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…However, a recent study, based on sequence data and morphology, suggested it to be an endemic species with a vulnerable conservation ranking ( Shepherd et al 2023 ). Thus, integrating research results from morphological classification, molecular systematics, ecology and other fields, holds significant guiding significance for the rapid and accurate identification of cryptic species ( Kabus et al 2023 ; Meghana et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study, based on sequence data and morphology, suggested it to be an endemic species with a vulnerable conservation ranking ( Shepherd et al 2023 ). Thus, integrating research results from morphological classification, molecular systematics, ecology and other fields, holds significant guiding significance for the rapid and accurate identification of cryptic species ( Kabus et al 2023 ; Meghana et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%